2012
DOI: 10.1590/s1516-35982012001200008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolizable energy values of diets supplemented with xylanase determined with laying hens

Abstract: -The objective of this study was to evaluate the effect of the supplementation of xylanase in diets with reduced energy level on the apparent metabolizable energy corrected for nitrogen, determined with laying hens at 14, 36, 60 and 80 weeks of age. Four digestibility trials were conducted, using 80 Hy-line W36 laying hens aged 14, 36, 60 and 80 weeks of age. Birds were distributed in a completely randomized design in 2 × 2 factorial arrangement (energy level × inclusion of xylanase), totaling four treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The literature shows the possibility of energy reduction of up to 200 kcal/kg of ME in the diet containing XP, which is higher than the absolute majority of reductions observed in the studies: up to 100 kcal of ME/kg (Souza et al, 2012), 120 (Iwahashi et al, 2011), 125 (Cowieson, 2010), 145 (Viana et al, 2011), and 154 kcal of ME/kg (Bobeck et al, 2014).…”
Section: Test1mentioning
confidence: 63%
See 1 more Smart Citation
“…The literature shows the possibility of energy reduction of up to 200 kcal/kg of ME in the diet containing XP, which is higher than the absolute majority of reductions observed in the studies: up to 100 kcal of ME/kg (Souza et al, 2012), 120 (Iwahashi et al, 2011), 125 (Cowieson, 2010), 145 (Viana et al, 2011), and 154 kcal of ME/kg (Bobeck et al, 2014).…”
Section: Test1mentioning
confidence: 63%
“…The increase in the metabolizability of PC is related to the reduction in the production of endogenous amino acids, demonstrating that xylanases are efficient in reducing this production through a secondary effect, in which they improve the use of the protein content resulting from diets, there by improving digestion processes and directly affecting the metabolizability of nutrients (Masey O'Neill et al, 2014). Therefore, supplementation with XC was effective in improving the metabolizability of proteins, and consequently, their absorption due to the action of anti-nutritional factors (Souza et al, 2012).…”
Section: Testmentioning
confidence: 99%
“…Evaluating four xylanase inclusion levels (0, 200, 400 and 600 g/ton), Schoulten et al (2003) found that xylanase, at an adequate dose, is effective in reducing the negative effects caused by NSPs present in highly-viscous diets. Xylanase also has positive effects on low viscosity diets (Iwahashi et al, 2011;Souza et al, 2012;Khoramabadi et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Although xylanases are typically used in viscous grain diets (Mathlouthi et al, 2002;Schoulten et al, 2003;Tekeli et al, 2014), studies have also investigated its use with non-viscous or low viscosity grains (Iwahashi et al, 2011;Barbosa et al, 2012;Souza et al, 2012;Khoramabadi et al, 2014).In general, the inclusion of exogenous enzymes in poultry diets promotes a more efficient digestion, reducing maintenance energy requirements, as well as the amount of substrate that reaches the large intestine by improving substrate utilization in the small intestine, thereby altering the microbial population in the terminal ileum (Bedford & Apajalahti, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Xylanase is mainly responsible for the hydrolysis of xylan, the main constituent of plant cell wall hemicellulose, increasing digestive motility and reducing energy expenditure in digestion and absorption (Cowieson et al, 2010). According to Souza et al (2012), xylanase supplementation in laying hen diets resulted in an increase in apparent metabolizable energy (AME) and, consequently, improved the productive performance of the birds.…”
Section: Introductionmentioning
confidence: 99%